Prope legitimate rootstocks determine the selection criteria for drought-tolerant cocoa - Maera Zasari; Ade Wachjar; Agung Wahyu Susilo; Sudarsono Sudarsono (Society for Indonesian Biodiversity, 2020)
Abstract. Zasari M, Wachar A, Susilo AW, Sudarsono. 2020. Prope legitimate rootstocks determine the selection criteria for drought-tolerant cocoa. Biodiversitas 21: 4067-4075. Drought tolerant cocoa seedlings are needed for the success of cocoa cultivation under drought conditions. Prope legitimate rootstock is feasible to be used in the selection of drought-tolerant cocoa seedlings. This objective of this study was to determine the selection criteria and tolerance of prope legitimate cocoa rootstocks in response to drought stress. This study was conducted in the greenhouse of Kaliwining experimental garden, Indonesian Center for Coffee and Cocoa Research, Jember, Indonesia. Plant materials were arranged in a split-plot design with 2 factors and 6 replications. The main plot was the soil moisture content, i.e 100%, and 25%, while the subplots were 13 prope legitimate cocoa rootstocks. The result showed that root fresh weight was the best characters for the selection of drought tolerance in prope legitimate cocoa rootstock. Based on the value of stress susceptible index and clustering analysis divided the tested prope legitimate rootstock into two groups. The group for tolerant genotype was consisted of ICCRI 03, ICS 60, TSH 858, KKM 22, KW 641, KW 516, and MCC 02, while the sensitive genotype group was consisted of Sul 01, Sul 03, Sca 06, KEE 02, KW 617, and Sul 02.